Fabrication of Nanocellulose-EDTA Composite from Oil Palm Trunks for Cadmium Removal from Aqueous Solutions - Tiadeka, Pemta; Ratnasari, Diah; Mustikaningrum, Mega; Amilia Putri, Sasti; Lutiana (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2025)
The development of nanocellulose-based materials with enhanced properties has garnered significant interest among scientists. Oil palm trunks are a promising source of nanocellulose due to their high cellulose content, excellent adsorption capacity, and abundant availability. Cadmium, a toxic heavy metal, poses serious risks to environmental and human health. It accumulates in fish and plants, entering the human body through the food chain. Since cadmium resists natural degradation, effective removal methods are crucial to mitigate its hazardous effects. In this study, a functionalized nanocellulose composite (NCE) was successfully synthesized using ethylenediaminetetraacetic acid (EDTA) as a chelating agent to enhance cadmium adsorption in aqueous solutions. Analysis with FTIR confirmed the reaction between nanocellulose and EDTA, with characteristic bonds appearing at wavenumber 1100, 1172, and 48 cm⁻¹. Particle size analysis revealed polydisperse nanoparticles, with average sizes of 411.5 nm for nanocellulose and 665.3 nm for NCE. Microscopic imaging showed distinct morphological changes, indicating successful EDTA incorporation into the nanocellulose structure. NCE exhibited a high surface area (2.792 m² g-1). Atomic absorption spectroscopy showed a decrease in cadmium concentration, from 1 ppm to 0.2–0.3 ppm, indicating the adsorption ability of NCE. These findings highlight the potential of NCE for heavy metal remediation in water.